2011
DOI: 10.1292/jvms.11-0235
|View full text |Cite
|
Sign up to set email alerts
|

Sex Determination of Sika Deer (Cervus nippon yesoensis) Using Nested PCR from Feces Collected in the Field

Abstract: ABSTRACT. We describe a method for determining the sex of sika deer (Cervus nippon yesoensis) from feces collected in the field. Using a nested polymerase chain reaction (nested PCR), partial sequences of the sex determination region of the Y chromosome (SRY) gene and X zinc finger protein (ZFX) gene were amplified. In 19 individuals with sex information, the correct sex was successfully detected and sequences of target amplicons were completely matched between muscle and feces from the rectum. Among 75 fecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Our accuracy rate of sex determination was 80.2% of samples over 2 trials, which is comparable to the success rate observed for the SRY primer (85%) (Yamazaki et al, 2011). Further, the sex ratio detected here (1.27 female:1 male) corresponded to the ratio found in other field studies of blue sheep inhabiting Helan Mountain (Wang et al, 1998;Cao, 2005;Liu et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Our accuracy rate of sex determination was 80.2% of samples over 2 trials, which is comparable to the success rate observed for the SRY primer (85%) (Yamazaki et al, 2011). Further, the sex ratio detected here (1.27 female:1 male) corresponded to the ratio found in other field studies of blue sheep inhabiting Helan Mountain (Wang et al, 1998;Cao, 2005;Liu et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…To date, DNA from fecal samples of sika deer or Japanese serow was obtained using commercial DNA extraction kits (Horino and Nagata 2004;Yamazaki et al 2011) or the DNA extraction method described by Zhang et al (2006) (Yamashiro et al 2010). However, these methods require multiple reagents, expensive equipment, and they are laborious and time-consuming.…”
Section: Dna Extraction From Fecal Pellets and Muscle Tissuesmentioning
confidence: 99%
“…However, these methods require multiple reagents, expensive equipment, and they are laborious and time-consuming. The outer layer of the fecal pellet of sika deer contains a significant amount of DNA (Yamazaki et al 2011). Accordingly, to simplify the DNA extraction from fecal pellets of both animals, we did not use commercial DNA extraction kits or the method described by Zhang et al (2006).…”
Section: Dna Extraction From Fecal Pellets and Muscle Tissuesmentioning
confidence: 99%
“…Fecal molecular biotechnology provides a rapid and dependable way of sampling endangered animals [11][12][13][14]. In addition, with the development of molecular biology technology, fecal DNA is extensively used in genetic biology studies for species identification [15][16][17], individual identification [18][19][20], sex identification [21][22][23][24][25], population genetic structure [26][27][28], and genetic diversity evaluation [29]. However, fecal sampling has some problems, such as poor fecal DNA isolation quality and low success rate of PCR amplification [30].…”
Section: Introductionmentioning
confidence: 99%